Strategic HR Agility In Southeast Asian MSMES: A Cross-Country Study Of Indonesia, Vietnam, And The Philippines Amidst Digital Transformation - Anwar, Khairil; Nurrohman, Rosyid (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – This study aims to understand how Strategic Human Resource Agility (SHRA) is manifested and differentiated across Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, Vietnam, and the Philippines, particularly within the context of digital transformation. It explores the interplay between institutional readiness, digital HR practices, and cultural mindsets to map the current state of agile HR strategy among MSMEs in Southeast Asia. Novelty – The novelty of this research lies in its comparative framework that integrates secondary policy data, literature-based agility indicators, and qualitative thematic insights from recent studies between 2019 and 2024. Unlike prior works that often focus on large enterprises or single-country analysis, this study uniquely captures SHRA patterns across three ASEAN nations, offering a holistic macro–micro view. Method – This study adopts a qualitative-comparative method using secondary data sources such as ASEAN SME Index, World Bank, ILO, and national statistics agencies, supported by thematic synthesis from peer-reviewed literature. The analysis follows a case-based, cross-national approach supported by four structured data tables. Findings – The findings show that Vietnam leads in structured SHRA adoption due to stronger institutional coordination, while Indonesia lags despite a large MSME population. The Philippines displays moderate agility, with digital innovation concentrated in startup ecosystems. Across countries, digital HR tools remain underutilized. Limitations and Implications – This study is limited by its reliance on literature-based and secondary data, and its scope is restricted to three countries. However, it provides actionable insights for policymakers and MSME stakeholders to enhance HR agility as a pathway to inclusive digital development.